Human rights, legitimacy, and the use of force - Buchanan, Allen E., 1948- (Oxford University Press, 2010)
"The thirteen essays by Allen Buchanan collected here are arranged in such a way as to make evident their thematic interconnections: the important and hitherto unappreciated relationships among the nature and grounding of human rights, the legitimacy of international institutions, and the justification for using military force across borders. In Human Rights, Legitimacy, and the Use of Force Buchanan makes the case for a holistic, systematic approach, and in so doing constitutes a major contribution at the intersection of international political philosophy and international legal theory."--Jacket